Implementation of COVID-19 Laboratory Testing Certification Program (CoLTeP) in African Region - Maruta, Talkmore; Shumba, Edwin; Ndlovu, Nqobile; Moyo, Sikhulile; Bangure, Donewell; Kebede, Yenew; Noumedem Kenfack, Jaurès Arnaud (Frontiers in Public Health, 2022)
Objectives COVID-19 was declared a global pandemic in March 2020 with correct and early detection of cases using laboratory testing central to the response. Hence, establishment of quality management systems and monitoring their implementation are critical. This paper describes the experience of implementing the COVID-19 Laboratory Testing and Certification Program (CoLTeP) in Africa. Methods Private and public laboratories conducting SARS-CoV-2 testing using Polymerase Chain Reaction (PCR) were enrolled and assessed using the CoLTeP checklists. Results 84 laboratories from 7 countries were assessed between April 2021 to December 2021 with 52% of these from the private sector. 64% of them attained 5-stars and were certified. Section 4 had the highest average score of 92% and lowest of 78% in Section 3. 82% of non-conformities (NCs) were related to sample collection, transportation and risk assessments. Non-availability, inconsistency in performing, recording, instituting corrective actions for failed Internal and External Quality Controls were among major NCs reported. Conclusions Laboratories identified for SARS-CoV-2 testing by public and private institutions mostly met the requirements for quality and safe testing as measured by the COLTeP checklist.